Pengaruh Pemberian Tepung Daun Kelor (Moringa oleifera) Sebagai Pakan Benih Ikan Lele Sangkuriang (Clarias gariepinus) - Farid, Akhmad; Indriati, Putri Alfatika; Arisandi, Apri; Triajie, Haryo (Rekayasa, 2023)
Catfish is a suitable choice for cultivation because it is an economical and nutritious fish for growing children. Catfish are also easy to cultivate and grow fast. This research was conducted for 35 days with the aim to determine the effect of moringa leaf powder with different doses of 4 treatments on the growth and survival rate of catfish seeds. The treatment given was treatment K as a control without adding moringa leaf powder, treatment A with 90% pellets and 10% moringa leaf powder, treatment B with 85% pellets and 15% moringa leaf powder and the last treatment was treatment C with 80% pellets and 20% moringa leaf powder. This research also measured water quality during the research, with parameters measured namely temperature, Dissolve Oxygen (DO), Power of Hydrogen (pH), and ammonia. The results obtained stated that treatment C with addition of 80% pellets and 20% moringa leaf powder was the best results in all aspects, both growth  survival rate, feed convertion rasio and water quality, and fulfilled SNI (2014) regarding catfish.